If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) + -2(3x + -5) + 4x + -1 = 4(2x + -1) + -1(2x + 5) Reorder the terms: 3(4 + x) + -2(3x + -5) + 4x + -1 = 4(2x + -1) + -1(2x + 5) (4 * 3 + x * 3) + -2(3x + -5) + 4x + -1 = 4(2x + -1) + -1(2x + 5) (12 + 3x) + -2(3x + -5) + 4x + -1 = 4(2x + -1) + -1(2x + 5) Reorder the terms: 12 + 3x + -2(-5 + 3x) + 4x + -1 = 4(2x + -1) + -1(2x + 5) 12 + 3x + (-5 * -2 + 3x * -2) + 4x + -1 = 4(2x + -1) + -1(2x + 5) 12 + 3x + (10 + -6x) + 4x + -1 = 4(2x + -1) + -1(2x + 5) Reorder the terms: 12 + 10 + -1 + 3x + -6x + 4x = 4(2x + -1) + -1(2x + 5) Combine like terms: 12 + 10 = 22 22 + -1 + 3x + -6x + 4x = 4(2x + -1) + -1(2x + 5) Combine like terms: 22 + -1 = 21 21 + 3x + -6x + 4x = 4(2x + -1) + -1(2x + 5) Combine like terms: 3x + -6x = -3x 21 + -3x + 4x = 4(2x + -1) + -1(2x + 5) Combine like terms: -3x + 4x = 1x 21 + 1x = 4(2x + -1) + -1(2x + 5) Reorder the terms: 21 + 1x = 4(-1 + 2x) + -1(2x + 5) 21 + 1x = (-1 * 4 + 2x * 4) + -1(2x + 5) 21 + 1x = (-4 + 8x) + -1(2x + 5) Reorder the terms: 21 + 1x = -4 + 8x + -1(5 + 2x) 21 + 1x = -4 + 8x + (5 * -1 + 2x * -1) 21 + 1x = -4 + 8x + (-5 + -2x) Reorder the terms: 21 + 1x = -4 + -5 + 8x + -2x Combine like terms: -4 + -5 = -9 21 + 1x = -9 + 8x + -2x Combine like terms: 8x + -2x = 6x 21 + 1x = -9 + 6x Solving 21 + 1x = -9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 21 + 1x + -6x = -9 + 6x + -6x Combine like terms: 1x + -6x = -5x 21 + -5x = -9 + 6x + -6x Combine like terms: 6x + -6x = 0 21 + -5x = -9 + 0 21 + -5x = -9 Add '-21' to each side of the equation. 21 + -21 + -5x = -9 + -21 Combine like terms: 21 + -21 = 0 0 + -5x = -9 + -21 -5x = -9 + -21 Combine like terms: -9 + -21 = -30 -5x = -30 Divide each side by '-5'. x = 6 Simplifying x = 6
| 2x^2=7200 | | 79.49=100/6x | | -7x-27=8-1(1x-19) | | X/9=14/18 | | q^7-9q^5=0 | | ab-4a-4b+8=0 | | 5a+(-7)=-2 | | 4k-7+16=-3 | | 5x+20=24-3x-12 | | 7/(9-5i) | | 2x-4=3(-8-4x) | | 8-3x-(2x-4)=-3 | | (x^2y^3)/xy^4 | | 11/21*42 | | 3x-14y-7x-8y= | | 5910=(13790)r(5) | | (x/3)^2=729 | | a^4+49a^2=0 | | 9(x^2)-45x+56=0 | | 2w^2+11w-70=0 | | -2a(a-2b+5)= | | x/3^2=729 | | 2a=2b+4 | | 6=9+n | | 12x-46=-28+5x | | 3x/3=15/4 | | 8m+3=9+2m | | -6=-19+n | | 5x-3/3-x-2/5=7 | | -23=w/3-8 | | -5(6-x)+6=12-7(x+2) | | 2x/3-4/13=66/39 |